Serum Tumor Necrosis Factor Alpha and High Sensitive C-Reactive protein as Biomarkers in Periodontitis in Iraqi Patients with Osteoarthritis - Muhammad, Enas N; Saliem, Saif S; Naaom, Enas R (Journal of Baghdad College of Dentistry, 2018)
Background: Periodontitis (PD) is well-known chronic disease affecting the periodontal ligament and alveolar bone, Osteoarthritis (OA) is a chronic joint disease with compound reasons characterized by synovial inflammation, subchondral bone remodeling, also the formation of osteophytes, that cause cartilage degradation. Chronic periodontitis and osteoarthritis are considered widely prevalent diseases and related to tissue destruction due to chronic inflammation in general health and oral health. The aim of this study is todetermine the association of chronic periodontitis and osteoarthritits in patients by analysing tumor necrosis factor alpha TNFα and high sensitive c-reactive protein (hsCRP) in the serum. Materials and Method: A total of 80 patients of both sexes aged 35-50 years ,30 patients with osteoarthritis and moderate chronic periodontitis (CP+OA), 30 patients of both sexes aged 35-50 years with moderate chronic periodontitis alone (CP). And control group (C) of 20 healthy patients with healthy periodontium participated in this cross sectional study. we excluded the postmenopausal and pregnant woman from female patient and smoker patient also. All patients are free of medication and have good general health with no history of systemic disease. Participants with OA have documentation or radiographic imaging, consistent with degenerative arthritis in the absence of an inflammatory condition. Venous blood samples were drawn from each subject using pyrogen-free heparinized collection tubes. Tubes were centrifuged according to the manufacturer’s guidelines, then stored at -15°C till analyse. serum TNFα and hs CRP were measured using an enzyme-linked immunosorbent assay (ELISA). Results: A non-significant differences between studied group regarding serum level of hsCRP and TNF-α, as well as, the result revealed that the median of serum levels of hsCRP were little higher in chronic periodontitis with osteoarthritis group than chronic periodontitis group and control groups represent as 0.31, 0.29, and 0.24. Similarly, the medium serum level of TNFα was higher in chronic periodontitis with OAthan in other two groups (10.615, 10.533, and 9.682 respectively). The age and gender showed a non-significant difference between the groups Conclusion: The present study revealed that there’s a strong positive correlation between serum levels of hsCRP and TNFα in patients of all groups but there is no correlation between Osteoarthritis and chronic periodontitis.